Influence of light on serum cholesterol levels in complete (by birth) blind people - Rani, J. Sudha; Raju, D. S. S. K. (International Journal of Research in Medical Sciences, 2018)
Background: With blindness normal stimulation of the hypothalamic pituitary axis is reduced. The serum cholesterol is frequently increased the upper limit of normal it is unclear whether the effect is due to complete absence of light, HPA axis function reduction or diurnal variation of melatonin levels. Methods: A self-administered questionnaire ascertained lifestyle characteristics, including alcohol consumption, cigarette smoking, diabetes mellitus and dietary habits. Inclusion criteria: 50 complete blindness persons (by birth), healthy adults, Age group between 30-50 years. Exclusion area: age <30, Age >50, alcoholic, liver diseases, kidney diseases, diabetes mellitus, thyroid diseases. Results: A total No of 100 cases were studied by dividing them into two groups controls 50 and cases 50. The results so obtain were compared with 50 healthy controls (excluded consumed alcoholic, liver diseases, kidney diseases, diabetes mellitus, thyroid diseases.). Statistical evaluation was carried out to confirm any deviation from the normal values. The mean serum cholesterol of Cases (298.28±26.82) is having higher level as compared to the mean value of controls (153.38±11.79). This increase is statistically highly significant (<0.0001). Conclusions: It has been shown from this study with blindness normal stimulation of the HPA is reduced consequently the serum cholesterol is frequently increased the concentration may exceed the upper limit of normal. On this basis we observed increases the upper limit of the cholesterol levels in blind healthy people than subjects with normal healthy light perception.